Kyrgyz Republic : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2002)
This paper evaluates the Kyrgyz Republic's First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). All quantitative performance criteria have been observed, and the program is on track. The end-March net international reserves target was exceeded by 20 percent of reserve money, and net domestic assets remained below the program ceiling by 4 percent of reserve money. The program's fiscal performance criteria were also met. The program conditionality on structural reforms was satisfied.